2016
DOI: 10.1136/bmjopen-2016-013283
|View full text |Cite
|
Sign up to set email alerts
|

Estimating change in cardiovascular disease and diabetes burdens due to dietary and metabolic factors in Korea 1998–2011: a comparative risk assessment analysis

Abstract: ObjectivesOver the past 10 years, the burden of chronic diseases in Korea has increased. However, there are currently no quantitative estimates of how changes in diet and metabolic factors have contributed to these shifting burdens. This study aims to evaluate the contributions of dietary and metabolic risk factors to death from cardiometabolic diseases (CMDs) such as cardiovascular conditions, strokes and diabetes in Korea, and to estimate how these contributions have changed over the past 10 years (1998–2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
3
8
1
Order By: Relevance
“…18 Adherence to a healthier dietary pattern has also been associated with a lower mortality risk in Koreans, Japanese and Singapore Chinese. [19][20][21] Compared with Japan and Korea, the average consumption levels that we observed in China were much lower for fish, marine omega-3 fatty acid, and fruit and were higher in vegetables and PUFA. We also found that the Chinese population had lower intakes of SSBs and processed meat than Japanese or Koreans.…”
Section: Discussionmentioning
confidence: 54%
“…18 Adherence to a healthier dietary pattern has also been associated with a lower mortality risk in Koreans, Japanese and Singapore Chinese. [19][20][21] Compared with Japan and Korea, the average consumption levels that we observed in China were much lower for fish, marine omega-3 fatty acid, and fruit and were higher in vegetables and PUFA. We also found that the Chinese population had lower intakes of SSBs and processed meat than Japanese or Koreans.…”
Section: Discussionmentioning
confidence: 54%
“…A recent study from China [ 13 ] reported moderate improvements in consumption of refined grains, fruits, and nuts and seeds and unfavorable changes in consumption of processed meat and sugar-sweetened beverages from 1982 to 2012, suggesting a shift in nutrition intervention and policy priorities for chronic disease prevention over time in China. We previously reported the associations between six dietary factors (fruits, vegetables, whole grains, processed meat, red meat, and sodium) and the burden of cardiometabolic disease mortality from 1998 to 2011 in Korea [ 14 ]. In that study, high intake of sodium and low intakes of fruits and whole grains were found to be responsible for the highest number of deaths from cardiometabolic diseases during the study period [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the associations between six dietary factors (fruits, vegetables, whole grains, processed meat, red meat, and sodium) and the burden of cardiometabolic disease mortality from 1998 to 2011 in Korea [ 14 ]. In that study, high intake of sodium and low intakes of fruits and whole grains were found to be responsible for the highest number of deaths from cardiometabolic diseases during the study period [ 14 ]. Extending earlier studies [ 14 15 ], the present study examined the impact of nine dietary risk factors (fruits, vegetables, whole grains, processed meat, red meat, nuts and seeds, milk, sugar-sweetened beverages, and calcium), individually and collectively, on the burden of cardiometabolic disease and cancer mortality among Korean adults using nationally representative, repeated cross-sectional survey data from 1998 to 2016.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations